2018
DOI: 10.7748/ns.2018.e11078
|View full text |Cite
|
Sign up to set email alerts
|

An overview of developments in nurse prescribing in the UK

Abstract: In the UK and internationally, the nursing profession is continuing to advance and innovate its roles and functions. One area in which this is particularly notable is nurse prescribing. The UK has the most extended nurse prescribing rights in the world, with significant advances in this field over the past two decades. This article reflects on this development, what has been learned and the challenges that remain in relation to nurse prescribing and meeting healthcare service needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…A report of specialist diabetes services in 2007 found that 49% of hospital DSNs are involved in prescribing [18]. That is compared to the estimated 5% of the total United Kingdom nursing workforce in 2016 qualified as nurse independent or supplementary prescribers [36]. However, the necessity of DSNs to prescribe has been contested.…”
Section: Resultsmentioning
confidence: 99%
“…A report of specialist diabetes services in 2007 found that 49% of hospital DSNs are involved in prescribing [18]. That is compared to the estimated 5% of the total United Kingdom nursing workforce in 2016 qualified as nurse independent or supplementary prescribers [36]. However, the necessity of DSNs to prescribe has been contested.…”
Section: Resultsmentioning
confidence: 99%
“…Although the number of nurse IPs is much greater than pharmacist IPs, they only represent 5% of the nursing workforce, 35 while pharmacist IPs represent 7% of the pharmacist profession. 36 The fact that there are more nurse IPs than other professions is in line with the findings of other studies that have investigated the implementation of non-medical prescribing in England 33 37 and Wales.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of nurse education and practice, undergraduate education in the UK has been incorporated into the pharmacology curriculum (Page & McKinney, 2007). The Nursing and Midwifery Council (NMC) requires nurses applying for prescription authority to have a bachelor's degree (Courtenay, 2018) and at least 3 years of clinical experience (Prydderch, 2019). British nurses have been able to prescribe medicine and have experienced various complicated circumstances over the past 28 years with relatively mature experience.…”
Section: Discussionmentioning
confidence: 99%